Análisis de la aplicación del artículo 42 de la ley de comunicación en la contratación de personal profesional en las radios del cantón latacunga desde su promulgación en junio 2013 hasta junio 2014 - Quintana Riera, Carmita del Consuelo (2015)
In this research the effects of the application of Article 42 of the Communications Law in Latacunga radios are analyzed. The implementation of Article No. 42 and its effects on radio stations were established as variables apply an interview and a survey of managers and employees respectively. Quantitative and qualitative statistical methods were used, concluding that the Article is stimulating for the professional development of employees to evaluate their personal and family circumstances, confirming that with its implementation, changes take place in their working lives....